Primitive and committed human hematopoietic progenitor cells interact with primary murine neural cells and are induced to undergo self-renewing cell divisions - Gottschling, Sandra; Eckstein, Volker; Saffrich, Rainer; Jonáš, Alexandr; Uhrig, Markus; Krause, Ulf; Seckinger, Anja; Miesala, Katrin; Horsch, Kerstin; Straub, Beate Katharina; Ho, Anthony Dick (Experimental hematology, 2007)
Objective - Studies in animal models have indicated that hematopoietic progenitor cells (HPC) migrate and home to the central nervous system and might acquire neural features under specific circumstances. The interaction between HPC and the neural environment and the functional effect on hematopoiesis have not yet been defined. - Methods - CD34+133+ cells from mobilized peripheral blood were cocultured with primary murine neurons or astrocytes. Chemotaxis and adhesive interactions were studied by applying β1- and β2-integrin function-blocking anibodies. The impact of neural feeder layers on integrin expression of HPC and the presence of appropriate adhesion ligands on neural cells were determined by immunostaining and flow cytometry. The hematopoietic long-term fate was monitored by time-lapse microscopy of individual cell-division history followed by long-term culture-initiating cell (LTC-IC) and colony-forming cell (CFC) assays. Neural differentiation was assessed by immunostaining against specific neuronal and glial antigens. - Results - The 23.0% ± 4.9% of HPC showed stromal cell-derived factor-1-induced migration toward neural cells, and 20.2% ± 1.6% displayed firm β1-integrin-mediated adhesion to astrocytes. The latter expressed appropriate adhesion ligands, stabilized β1-integrin expression, and increased β2-integrin expression of HPC. Neural differentiation of HPC could not be identified but astrocytes were able to induce limited self-renewing cell divisions of HPC and thus maintain 25.8% ± 3.4% of the initial LTC-IC and 80.7% ± 1.9% of the initial CFC. - Conclusion - Human HPC are able to interact with neural cells and interaction maintains, albeit to a limited extent, the self-renewal capability of HPC.